H.U.B city steps: methods and early findings from a community-based participatory research trial to reduce blood pressure among african americans - Molaison Elaine; Reed Vickie; Wang Bo; Madson Michael B; Connell Carol C; Zoellner Jamie M; Yadrick Kathleen (BMC, 2011)
Abstract Background Community-based participatory research (CBPR) has been recognized as an important approach to develop and execute health interventions among marginalized populations, and a key strategy to translate research into practice to help reduce health disparities. Despite growing interest in the CBPR approach, CBPR initiatives rarely use experimental or other rigorous research designs to evaluate health outcomes. This behavioral study describes the conceptual frameworks, methods, and early findings related to the reach, adoption, implementation, and effectiveness on primary blood pressure outcomes. Methods The CBPR, social support, and motivational interviewing frameworks are applied to test treatment effects of a two-phased CBPR walking intervention, including a 6-month active intervention quasi experimental phase and 12-month maintenance randomized controlled trial phase to test dose effects of motivational interviewing. A community advisory board helped develop and execute the culturally-appropriate intervention components which included social support walking groups led by peer coaches, pedometer diary self-monitoring, monthly diet and physical activity education sessions, and individualized motivational interviewing sessions. Although the study is on-going, three month data is available and reported. Analyses include descriptive statistics and paired t tests. Results Of 269 enrolled participants, most were African American (94%) females (85%) with a mean age of 43.8 (SD = 12.1) years. Across the 3 months, 90% of all possible pedometer diaries were submitted. Attendance at the monthly education sessions was approximately 33%. At the 3-month follow-up 227 (84%) participants were retained. From baseline to 3-months, systolic BP [126.0 (SD = 19.1) to 120.3 (SD = 17.9) mmHg; p < 0.001] and diastolic BP [83. 2 (SD = 12.3) to 80.2 (SD = 11.6) mmHg; p < 0.001] were significantly reduced. Conclusions This CBPR study highlights implementation factors and signifies the community's active participation in the development and execution of this study. Reach and representativeness of enrolled participants are discussed. Adherence to pedometer diary self-monitoring was better than education session participation. Significant decreases in the primary blood pressure outcomes demonstrate early effectiveness. Importantly, future analyses will evaluate long-term effectiveness of this CBPR behavioral intervention on health outcomes, and help inform the translational capabilities of CBPR efforts.